Association of clinico-pathological and immunohistochemical prognostic parameters with presence of ductal carcinoma in-situ in an invasive ductal carcinoma of breast - Balaiya, Dhivya; Chellam Annadurai, Anitha; Subbiah Rajasekaran, Jayakarthiga (Journal of Pathology of Nepal, 2023)
Background: The clinical outcome of breast carcinoma varies in each individual due to its molecular heterogeneity. There is a rising interest in whether the associated ductal carcinoma in-situ in invasive ductal carcinoma of breast affects the prognosis and overall survival of the patient. This study evaluates the difference in clinico-pathological and immunohistochemical prognostic factors between invasive ductal carcinoma with associated in-situ component, and invasive ductal carcinoma alone.Materials and Methods: The study was conducted at a tertiary care hospital in South Tamilnadu, India. Two study groups were categorized based on the presence/absence of in-situ component in invasive ductal carcinoma of breast. Clinico-pathological variables and immunohistochemistry [Estrogen receptor (ER), Progesterone receptor (PR), HER2/neu and ki67] findings were compared between the two groups and statistical analysis was performed.Results: There were 25 cases in each group. A significant statistical difference in tumor size was observed between invasive ductal carcinoma associated with in-situ component (mean-3.6cm) and without in-situ component (mean-5.0cm). A higher proliferative index (60%) was seen in invasive ductal carcinoma alone. There was no difference in the expression of Her2neu between the two groups. A proportionate increase in premenopausal population (60%) and hormone receptor positivity (ER, PR) was observed in invasive ductal carcinoma associated with in-situ component.Conclusions: Invasive ductal carcinoma associated with ductal carcinoma in-situ shows a less aggressive behaviour compared to invasive carcinoma alone. Further studies of a larger scale need to be done which might help in identifying the subgroup for targeted therapy.